The effect of ethnoscience-based physics learning on students' analytical skills in cultural contexts - Nurussaniah Nurussaniah; Hendra Sulistiawan (Universitas PGRI Pontianak, 2024)
Ethnoscience-based learning integrates local cultural knowledge into science education, providing students with contextually meaningful learning experiences. This study investigates the effect of ethnoscience-based physics learning on students' analytical skills in cultural contexts. A quasi-experimental design with a non-equivalent control group was employed, involving 72 high school students in West Kalimantan, Indonesia. The experimental group received ethnoscience-based physics instruction incorporating Malay cultural practices and traditional knowledge systems, while the control group received conventional physics instruction. Analytical skills were measured using a validated instrument comprising 25 items aligned with Bloom's taxonomy (analysis level). Results revealed that students in the experimental group demonstrated significantly higher analytical skills compared to the control group (t = 4.87, p < 0.001, d = 1.12). Qualitative analysis of student reflections indicated that cultural contexts enhanced students' motivation to analyze physical phenomena. These findings suggest that ethnoscience-based physics learning is a promising pedagogical approach for developing analytical skills while preserving cultural heritage. Implications for curriculum development and teacher training are discussed.